The impact of Virtual Reality Headset (Oculus Rift CV1) to Enrich the Anatomy Course and Increase Motivation Among Medical Students - Alharbi, Amal Yahya (Journal of Educational and Psychological Sciences, 2022)
This research aimed to study the impact of virtual reality headset (VRH) (oculus rift cv1) to enrich the anatomy course and increase motivation among medical students, by using Quasi-experimental Design, for twenty randomly picked students who are studying third year in human medical in King Abdulaziz University, with five missions designed by the researcher giving to the students during the experiment when wearing VRH with (3D Organon VR Anatomy) application, the study data was collected by questionnaire on the effect of VRH on the anatomy course enrichment, observation cards and the RIMMS motivation scale. Study results showed that VRH can effectively enrich anatomy course in average of (m=4,77) and (95.4%), and increase their motivation rates to (m=4,79) and (95.8%), for the female medical students at King Abdulaziz University. Because the headset increased the immersion of the students and their enjoyment in studying anatomy, and facilitated their imagination and perception with understanding, interaction and control by providing a wide field of vision, also integrating it with the traditional environment allowed the students to learn independent self-learning, better than the traditional environment alone. The study recommended using VRH for medical students and to prepare the faculty members for VRH use and acceptance.